Weak form quadrature element method for accurate free vibration analysis of thin skew plates. (October 2015) - Jin, Chunhua; Wang, Xinwei
Abstract In this paper, a novel weak form quadrature element method (QEM) is proposed for accurate free transverse vibration analysis of thin isotropic skew plates with general boundary conditions. In the formulation of the stiffness matrix, the first and second order derivatives of the shape functions at integration points are computed explicitly by using the differential quadrature rule. This leads to a great simplicity in formulating an <alternatives><inline-graphic xlink:href="ark:/27927/pgj2svgs6pw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N×N</alternatives>-node quadrature plate element and a large reduction of programming effort. Different from the existing weak form quadrature element method or differential quadrature finite element method, the element nodes can be either the same or different from the integration points. Convergence studies are performed. Free vibration of skew thin plates with various skew angles and different combinations of boundary conditions is analyzed. It is shown that although the assumed displacement field does not explicitly consider the bending moment singularities at the obtuse angles, the proposed QEM can yield accurate frequencies even for the thin isotropic skew plate with large skew angles.